Harmoni Multikultural: Membangun Kebersamaan di Tengah Perbedaan untuk Kaum Milenial - Katarina Leba; Balthasar Watunglawar; Muhammad ‘Ariful Furqon; Dwi Wijonarko (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
This community service activity is conducted through a religious seminar to strengthen the understanding and implementation of diversity values among young generations. The seminar is designed to respond to the increasing challenges of societal polarisation and intolerance, especially among millennials. Through a series of interactive sessions, participants are invited to explore the concept of multicultural harmony from a religious perspective, emphasizing universal values such as compassion, empathy, and mutual respect. The seminar material covers discussions on the role of religion in promoting peace, strategies to overcome inter-group prejudices and stereotypes, and best practices in building interfaith dialogue. The seminar also addresses the role of technology and social media in facilitating positive interactions between cultures and religions. It is hoped that through this activity, millennials can become active agents of change in building a harmonious and inclusive society while respecting the uniqueness of each cultural identity. Post-seminar evaluations show increased participants' understanding of the importance of togetherness in diversity and a commitment to apply the values of multicultural harmony in daily life.